2005
DOI: 10.1261/rna.7174805
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide analysis of C/D and H/ACA-like small nucleolar RNAs in Trypanosoma brucei reveals a trypanosome-specific pattern of rRNA modification

Abstract: Small nucleolar RNAs (snoRNAs) constitute newly discovered noncoding small RNAs, most of which function in guiding modifications such as 2-O-ribose methylation and pseudouridylation on rRNAs and snRNAs. To investigate the genome organization of Trypanosoma brucei snoRNAs and the pattern of rRNA modifications, we used a whole-genome approach to identify the repertoire of these guide RNAs. Twenty-one clusters encoding for 57 C/D snoRNAs and 34 H/ACA-like RNAs, which have the potential to direct 84 methylations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
117
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(130 citation statements)
references
References 59 publications
11
117
2
Order By: Relevance
“…1B). The number of 2′-O methylations (66 sites) remarkably exceeds that in other eukaryotes, which is consistent with bioinformatics analysis (9) and the modifications on the Leishmania ribosome structure recently revealed (10).…”
Section: Resultssupporting
confidence: 84%
“…1B). The number of 2′-O methylations (66 sites) remarkably exceeds that in other eukaryotes, which is consistent with bioinformatics analysis (9) and the modifications on the Leishmania ribosome structure recently revealed (10).…”
Section: Resultssupporting
confidence: 84%
“…These variations stem from either a difference in the number of genes encoding for each snoRNA species or the efficacy of processing of the snoRNA within its cluster (42). Indeed, we have recently demonstrated that the numbers of different snoRNA clusters vary from 1 to 10, and therefore the copy numbers of individual H/ACA genes differ considerably (10). In addition, we noticed a difference in the level of snoRNAs emerging from the same polycistronic RNA, most probably as a result of differential processing efficacy (43).…”
Section: Resultsmentioning
confidence: 77%
“…However, we expect that such RNAs do exist. Recently, we described a genome-wide analysis of H/ACA RNA in T. brucei (10). However, among the 34 H/ACA-like molecules identified, we detected no small Cajal body-specific RNA (scaRNAs) or conventional RNAs that could guide ⌿ modification on U snRNAs (10).…”
Section: Modifications On U Snrnas Are Carried Out In Part By H/aca-imentioning
confidence: 91%
See 2 more Smart Citations